Forming and maintaining a collection of plant genetic resources of the Buckwheat (Fagopyrum Mill.) genus - О. В. Тригуб (Plant Varieties Studying and Protection)
Purpose. Providing information on the formation, composition, maintenance of the collection of Buckwheat (Fagopyrum Mill.) genus at Ustymivka Experimental Station of Plant Production (Poltava region), and areas of its use: introduction, preservation and study of the material, for the set of index, formation of special collections and providing research and education institutions of Ukraine with a valuable original material. Methods. Methodical developments dealing with formation and maintenance of crop collections, methodical literature on the study of buckwheat collection for breeding and agronomic performance. Results. The author represented results of the collection material study for the main breeding and economically valuable traits including yield, productivity, resistance to abiotic and biotic factors of the environment. The results of work are considered aimed on creating special collections of the gene pool – base, trait (for yield and large seeds; for productivity, drought and heat resistance; for suitability for mechanical cultivation), educational and core ones. Conclusions. All formed and registered collections are a valuable base material for solving a number of breeding goals to increase the quantity and improve the quality of plant production.